A study on prevalence of premarital sex among adolescent students - Singh, SK; Krishna, G; Manandhar, N; Singh, CM (Journal of Institute of Medicine Nepal, 2007)
Background: This is the base line study conducted among adolescent students of District Chitwan to correlate between the knowledge of students about HIV/AIDS and prevalence of premarital sex along with some other epidemiological variables. Methods: The present study is a cross sectional base line study conducted among adolescent students of randomly selected twelve higher secondary schools of Chitwan district in January 2005. Results: Despite the satisfactory knowledge about HIV/AIDS, prevalence of premarital sex was quiet high (18.32%). It was more common among boys (25.8%) than girls (9.2%) and it was consistently increasing with increase in age. It was most common among Hindus adolescents (19.0%) and least among Christians. Parent’s education played very important role in reducing the practice of premarital sex as it was revealed in this study 81.76% of the adolescents had practiced safe sex and used condom and 22.32% of them properly disposed of it after use. Conclusion: It was satisfying that most of the adolescents who practiced sex, were protected by using condom but the correct disposal was not known to majority that’s why they disposed it indiscriminately by throwing on the road or the left ground. Key words: Adolescents, Premarital sex, Condom The full text of this paper is available at Journal of Institute of Medicine website